Construction of the waaF Subunit and DNA Vaccine Against Escherichia coli in Cow Mastitis and Preliminary Study on Their Immunogenicity - Wang, Hua; Yuan, Ligang; Wang, Tao; Cao, Lu; Liu, Fukang; Song, Juanjuan; Zhang, Yong (Frontiers in Veterinary Science, 2022)
Escherichia coli (E. coli) are one of the pathogenic bacterias of cow mastitis, which mainly triggers systemic symptoms by releasing lipopolysaccharide (LPS). The waaF is the core sequence of LPS pathogenicity and is highly conserved. In this study, the waaF gene was extracted and amplified from E. coli in milk to construct and purified the eukaryotic expression vector pcDNA3.1(+)HisB-waaF. After transfecting into the MCF-7 cells to purify the recombined protein waaF, the safety of the two vaccines was evaluated in mouse models for the first time. After that, the IgG content of serum, sIgA content of feces, serum cytokine levels (interleukin-2, interleukin-4, and interferon-γ) and mortality of challenged mice were compared to validate the effectiveness of the two vaccines in 20μg and 40μg, respectively. The results show that the waaF recombined protein and plasmid were constructed successfully and the mice who had been evaluated for safety did not show any abnormal behavioral changes and histopathological lesions after vaccination. Furthermore, the waaF recombined protein could be highly effective in immunogenicity and immunity protection, besides which, the 20μg waaF recombined protein is more economical. Comparing the safety, immunogenicity, and E. coli challenge of the two forms of vaccine that the waaF recombined protein had the better effect. In conclusion, this study provided a theoretical basis for the development of a new vaccine for dairy cow mastitis, and provided for the prevention and treatment of dairy cow mastitis candidate vaccines.